Scholarship and anti-scholarship - MacEoin, Denis 1949- (1986)
Hatcher, William S. ; Martin, J. Douglas: The Baha'i faith : the emerging global religion. - San Francisco/Cal. (u.a.) : Harper & Row, 1984. - XVII,226 S. - ISBN 0-06-065441-4
Review of the book "The Baha'i faith: the emerging global religion" by William S. Hatcher and J. Douglas Martin. 'Islamic background' to Baha'ism not properly stressed in the book. Influence of Shi'ism in Iran during the 19th century on the emergence of Baha'ism. Persecution of "Baha'is" in Iran. Relationship between Babism and Baha'ism. (DÜI-Sen)
Keywords: Religion; Islam; Strafverfolgung; Politische Verfolgung; Schiiten; Iran -- Bahaismus -- Religion -- Islam -- Strafverfolgung -- Politische Verfolgung -- Schia -- Islamische Länder/Islamische Welt; Iran; Islamische Staaten